2013
DOI: 10.3390/md11114232
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Diversity as a Function of Temperature in Six Northern Diatom Species

Abstract: In this study, we investigate how metabolic fingerprints are related to temperature. Six common northern temperate diatoms (Attheya longicornis, Chaetoceros socialis, Chaetoceros furcellatus, Porosira glacialis, Skeletonema marinoi, and Thalassiosira gravida) were cultivated at two different temperatures, 0.5 and 8.5 °C. To exclude metabolic variations due to differences in growth rates, the growth rates were kept similar by performing the experiments under light limited conditions but in exponential growth ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 34 publications
1
11
0
1
Order By: Relevance
“…Strain M21 seemed especially interesting and promising, as it had a high growth rate of 0.7 d − 1 at low temperatures (10 °C) and a high EPA content relative to biomass DW, which increased in stationary phase to 4.6%. Similar, but slightly lower growth rates (0.6 d − 1 ) at 8.5 °C have been reported for another Attheya species, A. longicornis , isolated from northern Norwegian coastal waters [49] . Additional investigations might reveal if it is possible to increase the EPA levels further, suggesting sampling later in the stationary phase and varying growth conditions.…”
Section: Resultssupporting
confidence: 82%
“…Strain M21 seemed especially interesting and promising, as it had a high growth rate of 0.7 d − 1 at low temperatures (10 °C) and a high EPA content relative to biomass DW, which increased in stationary phase to 4.6%. Similar, but slightly lower growth rates (0.6 d − 1 ) at 8.5 °C have been reported for another Attheya species, A. longicornis , isolated from northern Norwegian coastal waters [49] . Additional investigations might reveal if it is possible to increase the EPA levels further, suggesting sampling later in the stationary phase and varying growth conditions.…”
Section: Resultssupporting
confidence: 82%
“…This strategy, termed OSMAC (One strain–many compounds), has successfully been applied for drug discovery in bacteria 47 and could also work in microalgae. The production of primary and secondary metabolites in microalgae can vary depending on several factors 48 , such as growth phases 49 , strains 50 , light 51 , temperature 52 , culturing media 53 , grazing pressure 54 and extraction method 55 . This metabolic plasticity positively influences bioactivities and hopefully leads to the discovery of novel bioactive compounds for the treatment of human diseases.…”
Section: Discussionmentioning
confidence: 99%
“…temperature and light 3 . Other authors have also reported changes in bioactivity due to variation in environmental conditions like temperature 86 and light 87 . Biologically, the content of our samples and the chlorophyll measurements indicated differences in spring - bloom stage, with the Finnmark coast probably being in a post bloom stage, the Hopen area in a late bloom stage while we faced a vigorous ice-edge bloom in the Svalbard North West area (See Supplementary Figure S3 ).…”
Section: Discussionmentioning
confidence: 96%